2003
DOI: 10.1016/s0002-9440(10)64335-0
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Caveolin-1 Sensitizes Mouse Skin to Carcinogen-Induced Epidermal Hyperplasia and Tumor Formation

Abstract: Caveolin-1 is the principal protein component of caveolae membrane domains, which are located at the cell surface in most cell types. Evidence has accumulated suggesting that caveolin-1 may function as a suppressor of cell transformation in cultured cells. The human CAV-1 gene is located at a putative tumor suppressor locus (7q31.1/D7S522) and a known fragile site (FRA7G) that is deleted in a variety of epithelial-derived tumors. Mechanistically, caveolin-1 is known to function as a negative regulator of the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
127
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(137 citation statements)
references
References 44 publications
9
127
1
Order By: Relevance
“…Also, Caveolin-1 expression is reduced in several human tumors, including lung [29], mammary [30], colon [15,31] and ovarian carcinomas [32], as well as sarcomas [32] and re-expression of Caveolin-1 often (but not always) results in reversal of characteristics associated with the transformed phenotype. Consistent with these results, lung hyperplasia and predisposition to mammary, as well as carcinogen-induced skin hyperplasia and tumor formation are observed in Caveolin-1 knock-out mice [4][5][33][34][35]. These results indicate that Caveolin-1 displays properties and characteristics of a tumor suppressor molecule in a variety of cellular settings.…”
Section: The Tumor Suppressor Hypothesissupporting
confidence: 73%
See 1 more Smart Citation
“…Also, Caveolin-1 expression is reduced in several human tumors, including lung [29], mammary [30], colon [15,31] and ovarian carcinomas [32], as well as sarcomas [32] and re-expression of Caveolin-1 often (but not always) results in reversal of characteristics associated with the transformed phenotype. Consistent with these results, lung hyperplasia and predisposition to mammary, as well as carcinogen-induced skin hyperplasia and tumor formation are observed in Caveolin-1 knock-out mice [4][5][33][34][35]. These results indicate that Caveolin-1 displays properties and characteristics of a tumor suppressor molecule in a variety of cellular settings.…”
Section: The Tumor Suppressor Hypothesissupporting
confidence: 73%
“…In NIH3T3 fibroblasts, down-regulation of Caveolin-1 using specific siRNA is sufficient to hyperactivate the MAPK/ERK pathway and induce cell transformation [78]. Also, in Caveolin-1 knock-out mice, signaling via the MAPK/ERK pathway is increased and associated with increased sensitivity to topically applied carcinogens, cardiac hypertrophy and neointimal hyperplasia [33,[87][88]. Moreover, in human head and neck squamous cell cancer, Caveolin-1 inhibits the ERK pathway and cell growth [89], and in human laryngeal carcinoma cell lines, Caveolin-1 interaction with the EGFR is associated with reduced MAPK/ERK phosphorylation and increased apoptotic cell death [90].…”
Section: The Ras/raf/erk Connectionmentioning
confidence: 99%
“…However, caveolin-1 has also been found to be downregulated in tumours themselves, and several independent studies have shown that the re-expression of caveolin-1 in transformed cells inhibits features of the transformed phenotype, such as anchorage-independent growth. Caveolin-1 knockout mice also support the hypothesis, as they display hyperproliferative disorders and hyperactivation of the MAPK cascade, and are at greater risk from carcinogeninduced tumorigenesis [188]. Although these mice do not spontaneously form tumours, knockouts of important cell cycle control agents, such as the cyclin-dependent kinase inhibitor p21, also do not form tumours [206].…”
Section: Caveolin-1 Levels Are Not Always Reduced In Transformed Cellsmentioning
confidence: 79%
“…In addition, Capozza et al [188] found that caveolin-1 knockout mice were more susceptible to skin carcinogenesis induced by a known carcinogen, 7,12-dimethylbenzanthracene (DMBA).…”
Section: Caveolin Knockout Micementioning
confidence: 99%
“…54 In addition, Cav-1-deficient mice show the same phenotype, with increased ketone body production systemically 48 and increased numbers of stem cells in the skin, gut, mammary gland and brain. [55][56][57][58][59][60] In the brain, astrocytes produce mitochondrial fuels (L-lactate, ketone bodies and glutamine), which are then consumed by oxidative mitochondrial metabolism in neurons. 61 In addition, Figure 13.…”
Section: Methodsmentioning
confidence: 99%